Relação de parentesco dos golfinhos-rotadores (Stenella longirostris) do Arquipélago de Fernando de Noronha, PE, Brasil. - Pereira, Manoela da Silva (2023)
Studies on kinship can demonstrate an impact on the delineation of the social structure of species, being one of the main components of population biology. In the present work, both mitochondrial (mtDNA) and nuclear (nDNA) DNA were used with the aim of determining the kinship relationships between the spinner dolphins of the Fernando de Noronha Archipelago and the behavioral, adaptive and reproductive aspects associated with them. Samples of 266 live animals were collected in the Mar de Dentro region of the Archipelago, using the skin scraping method, in the years 2006, 2009, 2012, 2019 and 2022. From a 313 bp fragment of the control region of the mtDNA it was possible to detect 12 haplotypes in this population, with the prevalence of two main ones sampled in all collection campaigns. Analysis of seven nDNA microsatellite loci revealed relationships between 164 individuals, both first degree (full siblings or parent-child) and second degree (half-siblings). Relationships between spinners of different haplotypes, groups and between dolphins with possible marks were also evaluated. The mean relatedness between females was higher than that between males. These findings suggest that this population has a matrilineal basis, where family cells are composed of individuals from different mtDNA lineages, possibly presenting female philopatric behavior. In addition, the largest numbers of spinners seem to be concentrated in the Entre Ilhas region of the Archipelago, indicating a preference for this location, as already described in previous studies. These results resulted in the deepening of knowledge of the social genetic structure of this population and consequently can help in decision-making for conservation of this species in the region.